2015
DOI: 10.1097/mcg.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

A Scoring System for Predicting Significant Fibrosis in Chronic Hepatitis B Patients With Normal or Mildly Elevated Alanine Aminotransferase Levels

Abstract: The proposed fibrosis scoring system predicted the probability of significant fibrosis in CHB patients with ALT levels 2-fold lower than the ULN with sufficient accuracy. It identified individuals with a very high risk for significant fibrosis in whom liver biopsy would most likely yield a diagnostic benefit. It also identified individuals with a low risk of moderate fibrosis in whom a liver biopsy can be delayed or avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 1 publication
3
16
0
Order By: Relevance
“…37 An increased AST level with progression of liver fibrosis had been previously reported in a study of 283 CHB patients with ALT < 2ULN, which noted that AST levels were independent predictors for significant fibrosis. 7 Our findings were consistent with results from previous studies, which indicated that AST level was a better predictor of moderate or severe inflammation or significant fibrosis than ALT.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…37 An increased AST level with progression of liver fibrosis had been previously reported in a study of 283 CHB patients with ALT < 2ULN, which noted that AST levels were independent predictors for significant fibrosis. 7 Our findings were consistent with results from previous studies, which indicated that AST level was a better predictor of moderate or severe inflammation or significant fibrosis than ALT.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the development of noninvasive approaches for predicting liver inflammation or fibrosis based on LSM and serum markers, either alone or in combination, such as AST‐to‐ALT ratio (AAR) and aspartate aminotransferase‐to‐platelet ratio index (APRI), decreases the need of liver biopsy . However, all approaches are used to detect inflammation or fibrosis separately, rather than simultaneously . Furthermore, only a few articles have evaluated the performance of noninvasive models and there is no approach that is associated with antiviral therapy decision‐making in CHB patients with ALT < 2ULN …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in CHB patients with ALT < 2 × ULN, few non-invasive approaches have been developed to evaluate liver fibrosis[14,19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that AST has better diagnostic performance than ALT in predicting hepatic necrotizing in ammation [17]. As an independent factor to predict signi cant brosis, AST level increased with the aggravation of liver brosis [21]. Some of the delay clearance in AST was related to ALT level [22], and some of the advanced liver brosis was related to mitochondrial damage [23].…”
Section: Discussionmentioning
confidence: 99%